Pengaruh Kualitas Pelayanan, Nilai Pelanggan dan Harga Jasa Terhadap Kepuasan Konsumen PT.Pos Indonesia (PERSERO) Pada Kota Probolinggo - Hasanah, Riskiyatul; Hermawan, Dedi Joko; Priantono, Seger (Universitas Panca Marga, 2024)
This research was conducted at PT. Pos Indonesia (Persero) Probolinggo City with the aim of testing the significant partial, simultaneous and dominant influence of Service Quality (X1) Customer Value (X2) Service Price (X3) and Customer Satisfaction (Y) and to test which The dominant influence is the variable Service Quality (X1), Customer Value (X2), Service Price (X3) on Consumer Satisfaction (Y) PT. Pos Indonesia (Persero) Probolinggo City. The type of research in this research is quantitative research with a causal approach. The variables used include the influence of service quality (X1), service price (X2), customer value (X3) and consumer satisfaction (Y). The data used in this research are primary data and secondary data. The population in this study are all consumers who have used goods delivery services at PT. Pos Indonesia (Persero) Probolinggo City in February 2024 because the population is so large that the number cannot be known. The sample calculation uses the accidental sampling formula because the population is large, namely consumers who come to PT. Pos Indonesia (Persero) Probolinggo City. Data collection using questionnaires and documentation. The data analysis method uses validation tests, reliability tests, classical assumption tests, multiple linear analysis, coefficient of determination, t test, f test and dominant test with the help of SPSS version 26. Based on the results of testing the hypothesis, it shows that Service Quality, Customer Value, Service Price and Consumer Satisfaction influence the decision to use PT. Pos Indonesia (Persero) Probolinggo City services.